Salvation at stake: Christian martyrdom in early modern Europe by Brad S. Gregory - Frederick Hale (Acta Theologica)
From text: This prize-winning work represents classic scholarship in church history on a grand scale. Born in the early 1990s as a doctoral dissertation project at Princeton University, Gregory’s study matured through extensive postdoctoral research in the United Kingdom, the Low Countries, and France into what must be regarded as one of the more impressive analyses, in terms of both breadth of scope and depth of analysis to be published in the field in many years.